Implementation Of Emotional Design Aspects In The UI/UX Design Of A Local Fashion MSME E-Commerce Platform In Manado City - Rifky Ramadhan Masloman; Chriestie E.J.C Montolalu; Stephano Caesar Wenston Ngangi (International Journal of Health Engineering and Technology, 2026)
The rapid growth of e-commerce has increased the demand for user interfaces that are not only easy to use but also capable of providing positive emotional experiences for users. In Manado City, local fashion brands still face challenges in promoting their products and establishing their brand identity through digital platforms. This study aims to design a UI/UX prototype for a local fashion e-commerce platform by applying the principles of Emotional Design. This research employed a mixed-methods approach using the Design Thinking methodology, which consists of the empathize, define, ideate, prototype, and testing stages. Data were collected through a pre-survey, observation, literature review, and prototype evaluation using Maze, the User Experience Questionnaire (UEQ), and the System Usability Scale (SUS). The result of this study is a prototype of a local fashion e-commerce application called Urbanua, designed based on the visceral, behavioral, and reflective aspects of Emotional Design. The prototype provides various features that support both buyers' and sellers' needs while delivering a more engaging, user-friendly experience and strengthening the identity of local fashion brands. The findings indicate that applying Emotional Design in UI/UX design can produce an e-commerce prototype that meets user needs, enhances user experience, and supports the promotion of local fashion brands in Manado City.